Tinea Inkognito – Diagnosis dan Tata Laksana - Alvina Rusmayuni; Limyanti Dwi Vicaria (Cermin Dunia Kedokteran, 2024)
Misuses of high potency steroids which are easily accessible without doctor’s prescription and without any fungal examination, may cause tinea incognito. The term tinea incognito refers to dermatophytoses that have lost their classic clinical appearance; it may lead to misdiagnosis. Tinea incognito may imitate other dermatological diagnoses with polymorphic manifestations, including well-circumscribed round or oval lesion, vesicles and scales. Treatment requires cessation of all steroid use and effective antifungal treatment. Alvina Ulfah Rusmayuni, Limyanti Dwi